Screen as Skin: The Somatechnics of Touchscreen Music Media. (March 2017) - Glitsos, Laura
Abstract : In this article I explore the way mobile music devices with touchscreen technology produce new somatechnical figurations that reshape emotional dynamics of music listening. Using research drawn from a cyberethnography of online users from Reddit.com, I argue that the changing relationships between the human-computer interface result in new affective schemas that expand and reconfigure how it feels to listen to music in a mobile setting. In particular, I focus on skin-on-screen contact in order to suggest that the screen acts as a reflexive surface producing intimate relations for the mobile listener. Touchscreens imply the relationship between skin on skin—the skin of our body (in particular the hands) against the skin of the screen. It follows that mobile touchscreen devices suggest a degree of sensuality—in the coming together of bodies, fluids and other organic materials which 'stick' to the touchscreen. Reading the mobile touchscreen player as a somatechnical figuration therefore suggests that the listening experience is developing along with the technologies that mediate music to the body in ways that continue to challenge our understanding of bodily borders and in ways that redefine what it means to feel the music. Therefore, the touchscreen-skin is a critical site of affective relations that dramatically reshape what it means to listening to music in a mobile setting; a private and intimate encounter between the user and their counterpart.